Pickering syndrome: a rare presentation in emergency department. Issue 2 (9th February 2021) - Shrimal, Prawal; Sahu, Ankit Kumar; Mathew, Roshan; Bansal, Abhinav
Abstract : Sympathetic crash acute pulmonary edema (SCAPE) is a life-threatening injury, which requires early recognition and intervention to prevent mortality. We present a case of 18-year-old woman with no previous comorbidity, presenting with SCAPE who was successfully resuscitated and eventually diagnosed with renal artery stenosis. Pickering syndrome is a rare cause of hypertensive emergency and should be considered in a young patient presenting with SCAPE in emergency department.